Case study to document the condition of McConnell creek and the effect of redcedar revetments - Molina Gonzalez, Jose Antonio (Kansas State University, 2021)
Rivers are complex bodies of water under constant stress and factors such as land management increase the rate in which the channel is modified. Changes in land cover/land use are capable of modifying the hydrology of a site, accelerating the natural erosion rates of the stream banks and decreasing water quality. This case study was conducted to document overall creek condition at McConnell Creek in Wichita, Kansas and estimate the effect of streambank stabilization installations. The effects of the revetments were determined through two factors, first erosion/deposition rates on site, and second a bioassessment of macroinvertebrates. Erosion/deposition rates are measured through three different techniques. One method relied on dendrogeomorphology using exposed roots to quantify erosion for the previous 5-15 years based on the age of the roots, and when they were exposed. The macroinvertebrate bioassessment provides a better understanding of water quality, its degree of organic pollution and changes in biodiversity. The creek condition was determined through the use of the Rapid Assessment Along Stream Length (RASCAL) protocol which provided relevant background information of the creek’s ecological processes. Erosion/deposition rates on Revetment One (R1) showed a migration of upper sections of the cut bank being captured on the lower segments of the bank by the revetment. Macroinvertebrate sampling showed increased populations in areas where revetment installations where located but overall biodiversity decreased due to the presence of a dominant family Dogielinotidae. The RASCAL protocol yielded stream condition ratings on 64 reaches both on federal and private land. The RASCAL results show which areas treatment should be focused. Long term monitoring should be conducted to document the effects of the revetment.
Keywords: Redcedar; Macroinvertebrates; Erosion pins; Dendrogeomorphology; Rapid assessment along stream length